Quantifying the narration board for visualising final design concepts by interface designers - Wong, Chui Yin; Khong, Chee Weng (2007)
The narration board is a powerful design tool to help translate user observation studies into a storytelling format. It helps to communicate design values and ideas among the design team via visualising user scenarios in its proper context during the early design stages. This paper aims to discuss the narration board as a design tool to help the design team conceptualise and visualise user scenarios interacting with future design concepts within its context of use. Second part of the paper discusses how narration boards assist in generating ideations and visualising final design concepts by interface designers. Twenty (20) design projects (N=20) were examined to study and quantify two important factors, i.e. the components of the narration board in relation with the attributes of the final design concepts. A non-parametric correlation test was used to study the correlation coefficient between scores of the two factors. The results show that there is a statistically significant positive correlation between components of the narration board and attributes of the final design concept. Those with higher scores of components in narration board tend to produce better final design concepts, and vice versa.